2013
DOI: 10.1021/ja4015937
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Alkoxy Groups Substitution by Grignard Reagents on Aromatic Rings and Experimental Verification of Theoretical Predictions of Anomalous Reactions

Abstract: The mechanism of direct displacement of alkoxy groups in vinylogous and aromatic esters by Grignard reagents, a reaction that is not observed with expectedly better tosyloxy leaving groups, is elucidated computationally. The mechanism of this reaction has been determined to proceed through the inner-sphere attack of nucleophilic alkyl groups from magnesium to the reacting carbons via a metalaoxetane transition state. The formation of a strong magnesium chelate with the reacting alkoxy and carbonyl groups dicta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Secondly, electron‐rich aryl iodides could participate in the reaction, even with the electron‐deficient diarylzinc compounds. These results demonstrate that an aromatic nucleophilic substitution (S N Ar) process is less likely here 13. Since an electron‐withdrawing group on both 1 or 2 could enhance the reaction, it is conceivable that some critical anionic intermediates, which could be stabilized by electron‐withdrawing substituents, may be involved in the reaction.…”
Section: Resultsmentioning
confidence: 80%
“…Secondly, electron‐rich aryl iodides could participate in the reaction, even with the electron‐deficient diarylzinc compounds. These results demonstrate that an aromatic nucleophilic substitution (S N Ar) process is less likely here 13. Since an electron‐withdrawing group on both 1 or 2 could enhance the reaction, it is conceivable that some critical anionic intermediates, which could be stabilized by electron‐withdrawing substituents, may be involved in the reaction.…”
Section: Resultsmentioning
confidence: 80%
“…2h Encouraged by this, we focused on an unprecedented reaction route involving the “Ni 0 ‐ate complex”, which is completely different from the conventional mechanism (Scheme ). First, the reactants form an association complex CP1 with an energy loss (9.9 kcal mol −1 ) 22. At CP1 , PhOMe acted as a bridge for assembly of all the reactants: Ni 0 coordinates to the phenyl π plane, and PhMgBr forms a Lewis acid/base complex with ethereal oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…That the reaction was energetically feasible in spite of the disruption of aromaticity of the naphthalene moiety was contrasted with its failure in the case of isopropyl o-methoxybenzoate. 4e The mechanism of this unique, albeit long neglected, transformation was recently reported by Houk and Shaw, 7 and clarified based on theoretical calculations. Indeed, they showed that an inner sphere attack of nucleophilic groups from the reagent involved magnesium chelates.…”
mentioning
confidence: 86%
“…The reaction profile suggests second order kinetics (Grignard reagent) in agreement with an addition/elimination mechanism. Following the computational studies by Houk and co-workers with o-methoxynaphthyl esters and ketones, 7 the more bulky ketone 12 requires at least a sec-O OMe 3h: X = Br 99% 3i:…”
Section: Scheme 3 Scope Of the Nucleophilesmentioning
confidence: 99%